Dari Ritual Ke Panggung Pertunjukan: Perkembangan Tari Dalam Kehidupan Masyarakat - Tati Narawati (Humaniora, 2004)
There are three primary functions of dance in human life, i.e., for ritual,for personal entertainment, and for aesthetic presentation. All dance experts believe that the oldest function of dance in human life is for ritual. Dance is needed on the occasion of birth, circumcision, marriage, death, war, changes of the moon and sickness. Bali is the richest island of dance in Indonesia and known as "paradise in the world of arts. The Balinese dance ritual dances for gods, for spirits of the ancestors, for religious seers, for human beings, and also for the underworld spirits. Indonesia is rich in dance for personal entertainment, such as tayuban in Central and East Java, Jaipongan in West Java, gandrung in East Java, joget in Bali, ronggeng Melayu in Sumatera, etc. The development of urban population with sufficient income has influenced the development of dance as aesthetic presentation, because the urban people, categorized as the cultural consumers, need some aesthetic entertainment for their leisure time. The best country in the world whose amazing development of her dance as aesthetic presentation is the United States of America and New York is widely known as "the mecca of performing arts"